Changes in the structure and style of gondrang in Simalungun musical tradition - Nelson, Ricky (Talenta Publisher, 2025)
Gondrang is one of the most important musical ensembles in the Simalungun tradition, originally serving as sacred accompaniment in ritual contexts, particularly funerary ceremonies. Previous studies have largely focused on the social and cultural transformations of Gondrang, while the specific changes in its musical structure and style have not been analyzed in depth. This study aims to describe and analyze the internal musical changes of Gondrang, including its instrumentation, rhythmic organization, ensemble formation, melodic orientation, ornamentation, and performance expression. Employing a qualitative ethnomusicological approach, the research is based on observation of performances, interviews with musicians and cultural elders, and audio-visual documentation. The results show that Gondrang has experienced structural changes such as the addition of modern instruments and flexible ensemble settings, and stylistic changes including faster tempos, melodic expansion, ornamented improvisation, and more expressive performance gestures. Despite these changes, core rhythmic patterns and symbolic identity have been preserved. This study contributes to ethnomusicology by highlighting the internal dynamics of musical change, showing how Gondrang adapts to modern contexts while maintaining its cultural essence.